Responsibility For Error in Persona in Case of Wrong Shooting By Police Officers - Acmad Royani; Syamsul Arifin; Fajar Seto Nugroho; Dewi Indah Suryani (Jurnal Independent, 2026)
This study discusses Error in Persona , which is an error in determining legal subjects in criminal cases. This mistake has serious implications for the validity of the court decision and the protection of the rights of the accused. In the context of Indonesian criminal law, errors in identifying the perpetrators of criminal acts can lead to an unfair judicial process and even lead to the criminalization of innocent individuals. This study uses normative juridical methods with a legislative approach and case studies, to comprehensively understand the application of legal norms. The results of the study show that mistaken identity in criminal cases violates fundamental principles in the law, such as the principles of legal certainty, justice, and non-discrimination. In addition, such errors can have far-reaching legal consequences both for the integrity of the justice system and for the protection of human rights. To overcome this problem, it is necessary to strengthen the identification and verification mechanism from the investigation stage to the trial. This effort can be carried out through increasing the accuracy of population data, utilization in the process of identifying perpetrators of criminal acts. With these steps, it is hoped that errors in the determination of legal subjects can be minimized so that a more fair, accountable, and upholding the human rights of every citizen can be created.